Cases of replacing diffractive bifocal intraocular lens with extended depth of focus intraocular lens due to waxy vision - Ryu Takabatake (Public Library of Science (PLoS), 2021)
Purpose To investigate the postoperative course of patients who explanted a diffractive bifocal intraocular lens (IOL) due to waxy vision and implanted with an extended depth of focus IOL. Methods This study evaluated 29 eyes of 25 patients who underwent diffractive bifocal IOL explantation followed by TECNIS Symfony® implantation because of dissatisfaction due to waxy vision at the Takabatake West Eye Clinic between January 2018 and November 2019. The indication criteria for this surgery were patients with uncorrected distance visual acuity of 0.05 logMAR or better, without eye diseases that may affect visual function, and no dissatisfactions about photic phenomena. We investigated patient demographics, uncorrected and corrected visual acuity, manifest refraction, contrast sensitivity, subjective symptoms, time to IOL explantation, explanted IOL type, and spectacle independence. Results The time to the IOL exchange after the initial IOL implantation was 55.3 ± 50.4 days (range: 14–196 days). The logMAR corrected distance visual acuity before and after IOL exchange were −0.13 ± 0.06 and −0.14 ± 0.06, respectively (p = 0.273). After IOL exchange surgery, the area under log contrast sensitivity function increased significantly from 1.07 ± 0.12 to 1.21 ± 0.12 (p < 0.001), and the waxy vision symptoms improved. The spectacle independence rate at the last visit was 88.0%. Conclusion For patients who complain of waxy vision despite good visual acuity after diffractive bifocal IOL implantation, exchange to extended depth of focus IOL was considered one of the useful surgical options.